Determination of transition points and thermodynamic interaction parameters of poly(2,6-dimethyl-1,4-phenylene oxide) - Sakar, D.; Cankurtaran, O.; Karaman, F. (TAYLOR & FRANCIS LTD, 2008)
The specific retention volumes V-g(0) of n-butyl acetate, isobutyl acetate, isoamyl acetate, n-undecane, n-dodecane, n-tridecane, ethyl benzene, n-propyl benzene, isopropyl benzene and chloro benzene on poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) were obtained by inverse gas chromatography. Below glass transition temperature, two secondary transition points of PPO which occur at 90 and 130 degrees C were observed from the retention diagrams of n-butyl acetate, isobutyl acetate and isoamyl acetate. Weight fraction activity coefficient at infinite dilution Omega(infinity)(1), Flory-Huggins polymer-solvent interaction parameter chi(infinity)(12), hard core polymer-solvent interaction parameter chi(12)* and effective exchange energy parameter X-eff were determined from the experimental V-g(0) of studied solvents on PPO at temperatures above 220 degrees C by inverse gas chromatography.
Keywords: PPO; Second order transitions; Inverse gas chromatography; Thermodynamics; Solution properties; SECONDARY TRANSITIONS; POLYMER; Materials Science; Polymer Science